Specialized language data base incorporating the texts of the regional Belarusian newspapers - Rychkova, L.V.; Stankevich, A.Yu. (Мовознавство, 2018)
Main principles of creation of the full-text database incorporating the texts of regional
Belarusian mass-media being elaborated as an experimental basis within the framework
of the research project «Functioning of the Belarusian language in bilingual regional mass
media» are described. The choice of the bilingual regional newspapers texts as the authentic
language material is justified and the annotation system is explained. У статті описано головні засади створення повнотекстової бази даних, що
містить тексти регіональних білоруських ЗМІ і була розроблена як експериментальна основа в межах дослідницького проекту «Функціонування білоруської мови в двомовних регіональних засобах масової інформації». Обґрунтовується вибір двомовних регіональних газет як джерел автентичного мовного матеріалу і висвітлюється система анотування.